Panitumumab for the treatment of metastatic colorectal cancer: a review. (July 2015) - Del Prete, M; Giampieri, R; Faloppi, L; Bianconi, M; Bittoni, A; Andrikou, K; Cascinu, S
In recent years, the treatment of metastatic colorectal cancer (mCRC) has evolved significantly with the increase of new therapeutic options, leading to an improved median survival for these patients. In particular, the identification of molecular targets in tumor cells has led to the introduction of biological drugs for the treatment of mCRC. Panitumumab is a fully human monoclonal antibody that binds the EGF receptor of tumor cells and inhibits downstream cell signaling with antitumor effect on inhibition of tumor growth. Its use has been approved by randomized clinical trials as monotherapy in chemorefractory patients or combined with chemotherapy in the treatment of RAS wild-type mCRC, where it demonstrated a significant improvement in survival and response rate. The purpose of this review is to analyze the use and efficacy profile of panitumumab, particularly focusing on recently reported data on its use, and future perspectives in patients with mCRC.